ANALISIS HARGA SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 - Galuh Retno Palupi; Andreas Suhendi (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2020)
Profitability ratios are ratios to assess a company's ability to find profits. This ratio also provides a measure of the effectiveness of a company's management. This is shown by the profits generated from sales and investment income. Components of profitability ratios used by the author are Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS). In the case of this study, Real Estate and Property companies listed on the Indonesia Stock Exchange will be the object to be examined by the author. The results showed that Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) simultaneously had an effect on the stock price. It is known from the F test results where the value of Fresult is 10.074 and test T where the value of T-Test significance is less than the success rate value with the value t = 0.000 < α 0.05. In addition, it is also known that variables that affect the stock price are Earning Per Share. This is demonstrated by the results of the T-Test partial ROA having a Sig value of 0.659 and ROE has a value of Sig 0.803. The second value of the variable is greater than the probability value (α) 0.05, whereas the EPS variable has a value of Sig 0.000 smaller than the probability value (α) 0.05.